Would FSI Method Will Give More Details About AAA Rupture? - Altwijri, Omar (British Journal of Healthcare and Medical Research, 2023)
In this work, the information gained from using of fluid–structure interactions (FSI) method to assess the risk of abdominal aortic aneurysm rupture is investigated. The combination of finite element analysis (FEM) and compositional fluid dynamics (CFD), known as FSI, is widely regarded as the most advanced tool available for analyzing pressures and stresses within an aneurysm. However, it is also recognized as being both costly and time-consuming. In general, the accuracy of the solutions obtained using this method is heavily reliant on the quantity and quality of the grid elements employed. An important reason of performing this analysis is to investigate the controversial recommendations of adding blood flow inside the deformable models – which increases the cost and the time of the analysis – against using uniform pressure avoiding the complexity of blood flow analysis. Or using the blood flow analysis in a non-deformable aneurysm shape. The pressure acting on the inner wall is the major determinant of the wall stresses and it leads to wall deformation which will normally affect flow behavior. It is debated that pressure variations, due to fluid motion, can significantly affect wall stress results. And it is also debated that deformation of the aneurysm wall due to acting pressure can affect the blood flow behavior and lead to more or less pressure distribution on the wall. These controversial conclusions made the role of blood flow and FSI in varying the blood pressure in the aneurysm internal wall unclear and hence more investigations are required.